(untitled) (Vietnam Journal of Community Medicine, 2021)
Objective: To describe the situation and some related factors of physical activity among adults in Phan Dinh Phung ward, Thai Nguyen city in 2019. Method: a cross-sectional descriptive studies was conducted on 495 adults in Phan Dinh Phung ward, Thai Nguyen city. Data were collected by face-to-face interview using global physical activity questionnaire (GPAQ). Results: The rate of high-level physical activity in men was 62.1% and for women was 47.8%, with 43.8% of women and 62.1% of men achieving physical activity according to WHO recommendations. Age, location convenience, status of hypertension, diabetes, and cardiovascular disease were significant related factors of physical activity.